Optimization of Physiochemical Parameters during Bioremediation of Synthetic Dye by Marasmius cladophyllus UMAS MS8 Using Statistical Approach - Fatin Nur Sufinas, Bt Shuib; Ahmad, Husaini; Azham, Zulkharnain; Hairul Azman, Roslan; Tay, Meng Guan (Hindawi Publishing, 2016)
integral with products such as azo dye, anthrax, and dyestuffs. As such, these industries produce a lot of waste by-products that could contaminate the environment. Bioremediation, therefore, has become an important emerging technology due to its costsustainable, effective, natural approach to cleaning up contaminated groundwater and soil via the use of microorganisms. The use of microorganisms in bioremediation requires the optimisation of parameters used in cultivating the organism. Thus the aim of the work was to assess the degradation of Remazol Brilliant Blue R (RBBR) dye on soil using Plackett-Burman design by the basidiomycete, M. cladophyllus UMAS MS8. Biodegradation analyses were carried out on a soil spiked with RBBR and supplemented with rice husk as the fungus growth enhancer. A two-level Plackett-Burman design was used to screen the medium components for the effects on the decolourization of RBBR. For the analysis, eleven variables were selected and from these four parameters, dye concentration, yeast extract concentration, inoculum size, and incubation time, were found to be most effective to degrade RBBR with up to 91% RBBR removal in soil after 15 days.